Spinal Compression by Brown Tumor in Two Patients With Chronic Kidney Allograft Failure on Maintenance Hemodialysis (Iranian Journal of Kidney Diseases, 2010)
Brown tumors with non-neoplastic process are noticed in patients with end-stage renal disease suffering from a severe form of secondary hyperparathyroidism. Herein, we report a patient with chronic kidney allograft failure returned back to hemodialysis who experienced manifestations of cauda equina compression secondary to a lumbar brown tumor. Also, we had another patient on hemodialysis with a demineralized lesion affecting the cervical vertebrae. Although brown tumor is a rare complication, these two cases highlighted the importance of neurological symptoms in uremic patients. Spinal decompression surgery, in order to alleviate pressure on neurological structures, together with subtotal parathyroidectomy, were highly indicated.